Growth of Staphylococcus aureus MF 31 on the Top and Cut Surfaces of Southern Custard Pies - Preonas, D. L. (1969)
A Staphylococcus strain was inoculated on the top and cut surfaces of freshly baked Southern custard pies which were then packaged in a pasteboard carton and held at 30 C. Daily plate counts of surface sections 0.3 inch (0.76 cm) in thickness were made. The top surface inoculum showed a 24-hr lag time. This was due to the protective action of a top cakelike layer as shown by homogenization of the mix and coating of the surface. Substitution of all sweeteners with dextrose completely inhibited growth on the top surface. Further addition of dextrose to lower water activity (Aw) to 0.9 prevented growth on the cut surface as well, but such pies were organoleptically unacceptable. Growth on the top surface could also be prevented by 80 μg of undissociated sorbic acid per g in combination with 100 μg of undissociated propionic acid per g in the baked pie. Growth on the cakelike top surface was always retarded longer than on the cut surface provided the packaging allowed evaporation of surface moisture. Reducing the Aw of a different type of cream pie to 0.907 prevented top surface growth. It was concluded that baked cream pies with a cakelike top layer could be marketed with a “refrigerate after opening” label, provided the package maintains the moisture gradient caused by the surface skin and either a combination of 80 μg of undissociated sorbic acid per g and 100 μg undissociated propionic acid per g is present in the baked pie or the Aw of the baked pie is 0.920 or lower.